Microgrid architecture: a reliability constrained approach - Patra, S.B.; Mitra, J.; Ranade, S.J. (IEEE Power Engineering Society General Meeting, 2005, 2005)
Today's power delivery infrastructure is operating under extreme stress. The last few decades have seen minimal investment in infrastructure, and little has been done to prepare the ageing equipment for increasing load growths and the demands of open access. Consequently, the deployment of distributed energy resources (DER) is becoming an increasingly attractive alternative to the expensive and time consuming processes of upgrading and augmenting the transmission and distribution systems. DERs are small, modular sources (generation or storage) of energy which are often more efficient and controllable than traditional power plants. These devices are installed at or near centers of utilization. Eventually, as their penetration increases considerably, they are interconnected in a grid-like fashion for stability and enhanced reliability. These grids are called 'microgrids'. This paper presents a rational method of building microgrids optimized for cost and subject to reliability constraints. The method is based on dynamic programming and consists of determining the optimal interconnection between microsources and load points, given their locations and the rights of way for possible interconnections. A new approach, called 'unit link addition', is also introduced. The method is demonstrated using a 22-bus system.